Cells, Batteries and Electrical Devices

By installing a positive temperature coefficient material layer on the positive electrode sheet of the battery cell, the problem of thermal runaway after short circuit in the secondary battery is solved, and the battery is high safety and good electrochemical performance are achieved.

CN119029505BActive Publication Date: 2025-02-11BYD CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411476989.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Secondary batteries are prone to internal short circuits in overcharging, overdischarge, physical damage or high-temperature environments, resulting in thermal runaway and seriously affecting the safety of the battery.

Method used

The positive temperature coefficient material layer is provided on the positive electrode sheet of the battery cell. The resistance of the material layer is low when it is lower than the Curie point, but when the temperature exceeds the Curie point, the resistance increases rapidly, thereby rapidly decreasing after the short circuit inside the battery cell. Heat production power to reduce the risk of thermal runaway.

Benefits of technology

By introducing a positive temperature coefficient material layer into the battery cell, the risk of thermal runaway can be effectively reduced after internal short circuit, the safety of the battery can be improved, and the good electrochemical performance can be maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029505B_ABST
    Figure CN119029505B_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, and discloses a battery cell, a battery, and an electrical device, wherein the battery cell comprises: a negative electrode plate, wherein the negative electrode plate comprises a negative active material layer; a positive electrode plate, wherein the positive electrode plate comprises a positive current collector and a positive electrode tab, wherein the positive current collector is connected to the positive electrode tab, and a positive temperature coefficient material layer is provided on a side surface of the positive current collector facing the negative electrode plate near an edge of one end of the positive electrode tab; a diaphragm, wherein the diaphragm is located between the positive electrode plate and the negative electrode plate, wherein at least a portion of the positive temperature coefficient material layer's positive projection toward the negative electrode plate passes through the diaphragm and is located in the region where the negative electrode plate exceeds the positive electrode plate; and the positive projection of the positive electrode tab toward the negative electrode plate is located outside the negative electrode plate. The battery cell of the present application is not prone to thermal runaway after an internal short circuit occurs, thereby making the battery highly safe while having good electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to battery cells, batteries and electrical devices. Background Art

[0002] With the advancement of science and technology and the enhancement of consumers' safety awareness, secondary batteries must not only have high energy density and excellent electrochemical performance, but their safety has also become the focus of more and more attention. The reliability and safety performance of batteries have become important criteria for measuring their performance.

[0003] Secondary batteries may be overcharged, over-discharged, physically damaged or impacted, or exposed to high temperatures, which may cause internal short circuits. Once a short circuit occurs inside the battery, it may cause thermal runaway, a serious safety issue that may cause the battery to overheat or even catch fire or explode. Therefore, preventing internal short circuits and subsequent thermal runaway is a key issue in secondary battery safety research and needs to be addressed urgently. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a battery cell, a battery and an electrical device. The battery cell of the present application is not prone to thermal runaway after an internal short circuit occurs, so that the battery has high safety and good electrochemical performance.

[0005] In a first aspect, the present application provides a battery cell. According to an embodiment of the present application, the battery cell comprises: a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer;

[0006] A positive electrode sheet, the positive electrode sheet comprising a positive electrode collector and a positive electrode tab, the positive electrode collector being connected to the positive electrode tab, a positive temperature coefficient material layer being provided on a surface of one side of the positive electrode collector facing the negative electrode sheet near an edge of one end of the positive electrode tab, the positive temperature coefficient material layer comprising a positive temperature coefficient material;

[0007] A diaphragm, the diaphragm being located between the positive electrode sheet and the negative electrode sheet;

[0008] At least a portion of the positive temperature coefficient material layer's orthographic projection toward the negative electrode sheet is located in a region where the negative electrode sheet exceeds the positive electrode sheet; and the positive electrode tab's orthographic projection toward the negative electrode sheet is located outside the negative electrode sheet.

[0009] According to the battery cell of the embodiment of the present application, a positive temperature coefficient material layer is provided on the positive electrode plate, and its resistance is low when the temperature is below the Curie point, and the resistance increases rapidly after the temperature exceeds the Curie point. When the diaphragm is damaged and the negative electrode active material layer at the edge of the negative electrode plate contacts the positive electrode tab and the positive electrode current collector through the positive temperature coefficient material layer, an internal short circuit will occur due to the small resistance of the positive temperature coefficient material, generating a large amount of Joule heat, causing the internal temperature of the battery cell to rise. When the temperature exceeds the Curie point of the positive temperature coefficient material, the resistance of the positive temperature coefficient material increases, which will quickly reduce the heat generation power of the internal short circuit, allowing the battery's electrical energy to be released, and reducing the risk of thermal runaway after the internal short circuit of the battery cell. Thereby, the safety of the battery cell is improved.

[0010] According to an embodiment of the present application, the positive temperature coefficient material layer includes a positive temperature coefficient material, and the positive temperature coefficient material includes an organic matrix, an inorganic filler, and an adhesive filler.

[0011] According to an embodiment of the present application, the organic matrix includes at least one of polyethylene, polyethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polyhexafluoropropylene, polyhexafluoropropylene copolymer, polyamide, polyamide copolymer, polyurethane and polyurethane copolymer, and perfluoroethylene propylene copolymer.

[0012] According to an embodiment of the present application, the inorganic filler includes at least one of barium titanate and strontium titanate.

[0013] According to an embodiment of the present application, the adhesive filler includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and polyacrylate.

[0014] According to an embodiment of the present application, the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.2~0.9): (0.1~0.5): (0.05~0.2).

[0015] According to an embodiment of the present application, the surface of the positive electrode current collector facing the negative electrode plate further includes a positive electrode active material layer, and the positive electrode active material layer is connected to a side of the positive temperature coefficient material layer away from the positive electrode tab.

[0016] According to an embodiment of the present application, the positive electrode active material layer includes lithium iron phosphate or lithium manganese iron phosphate.

[0017] According to an embodiment of the present application, the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.35~0.5): (0.4~0.45): (0.1~0.2).

[0018] According to an embodiment of the present application, the positive electrode active material layer includes lithium iron phosphate, and the Curie point of the positive temperature coefficient material is 120° C. to 145° C.;

[0019] Alternatively, the positive electrode active material layer includes lithium manganese iron phosphate, and the Curie point of the positive temperature coefficient material is 115° C. to 136° C.

[0020] According to an embodiment of the present application, the positive electrode active material layer includes a ternary positive electrode material.

[0021] According to an embodiment of the present application, the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.7-0.85): (0.1-0.2): (0.05-0.1);

[0022] And / or, the Curie point of the positive temperature coefficient material is 90°C to 110°C.

[0023] According to an embodiment of the present application, the ternary positive electrode material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese aluminum oxide.

[0024] According to an embodiment of the present application, along the direction from the positive electrode current collector toward the positive electrode tab, the width of the positive temperature coefficient material layer is 1 mm to 5 mm.

[0025] According to an embodiment of the present application, the thickness of the positive temperature coefficient material layer is 20 μm to 60 μm.

[0026] The second aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes the battery cell described in the first aspect.

[0027] The third aspect of the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described in the second aspect.

[0028] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0030] Figure 1 A schematic diagram of the existing battery cell structure is shown;

[0031] Figure 2 A side view of the battery cell structure of the present application is shown;

[0032] Figure 3 A schematic diagram of the battery cell structure of the present application is shown.

[0033] Reference numerals:

[0034] 10: battery cell; 100: negative electrode plate; 110: negative electrode active material layer; 120: excess area; 130: negative electrode current collector; 140: negative electrode tab; 200: positive electrode plate; 210: positive electrode current collector; 220: positive electrode tab; 230: positive temperature coefficient material layer; 240: positive electrode active material layer; 300: separator. DETAILED DESCRIPTION

[0035] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0036] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0037] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0038] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0039] like Figure 1 As shown, in some secondary battery designs, the size of the negative electrode plate is larger than the positive electrode plate, forming an overhang area (also referred to as "overhang" in this application), which does not overlap with the positive electrode plate, and a portion of the overhang area (such as Figure 1 The overhang on the left side shown in the figure is isolated from the positive electrode tab by the diaphragm. During the use of the battery, the diaphragm may be damaged due to some factors, such as defects in the manufacturing process, lithium precipitation, volume changes during battery charging and discharging, material degradation caused by increased internal temperature, external shock or vibration to the battery, etc. Once the diaphragm is damaged, the negative electrode active material in the excess area will contact the positive electrode tab, causing an internal short circuit, thereby greatly increasing the risk of thermal runaway of the battery.

[0040] In order to reduce the risk of thermal runaway, a ceramic layer can be set on the surface of the positive electrode collector facing the negative electrode sheet, close to the edge of one end of the positive electrode ear. After the diaphragm ruptures, the negative electrode active material layer contacts the positive electrode ear and the positive electrode collector through the ceramic layer, which can prevent internal short circuits. However, the compatibility of ceramic materials with positive electrode active materials is poor, and there is uneven thickness in the coating area. In severe cases, a gap will appear between the positive electrode active material layer and the ceramic coating layer. In addition, the bonding strength between the ceramic material and the current collector is low, and the ceramic layer is prone to fall off.

[0041] Based on this, in the first aspect of the present application, a battery cell is proposed. Figure 2 A structural side view of a battery cell is shown. Figure 3 A schematic diagram of a battery cell structure is shown, wherein the battery cell 10 comprises a negative electrode sheet 100, a positive electrode sheet 200 and a separator 300; the negative electrode sheet 100 comprises a negative active material layer 110; the positive electrode sheet 200 comprises a positive current collector 210 and a positive electrode tab 220, the positive current collector 210 is connected to the positive electrode tab 220, a positive temperature coefficient material layer 230 is provided on a side surface of the positive current collector 210 facing the negative electrode sheet 100 near an end edge of the positive electrode tab 220, and the positive temperature coefficient material layer 230 comprises a positive temperature coefficient material; the separator 300 is located between the positive electrode sheet 200 and the negative electrode sheet 100, at least a part of the positive temperature coefficient material layer 230's orthographic projection toward the negative electrode sheet 100 is located in the region where the negative electrode sheet 100 exceeds the positive electrode sheet 200; the positive electrode tab 220's orthographic projection toward the negative electrode sheet 100 is located outside the negative electrode sheet 100. Figure 2 In the figure 120 , a region where the negative electrode sheet exceeds the positive electrode sheet is shown. This region may be referred to as a “exceeding region”. The orthographic projection of this exceeding region toward the separator is located inside the separator.

[0042] In this application, the term "positive temperature coefficient material" is interchangeable with "PTC material", which has a temperature below the Curie point and low resistance, and the resistance increases rapidly after the temperature exceeds the Curie point. When the diaphragm is damaged and the negative electrode active material layer at the edge of the negative electrode plate contacts the positive electrode tab and the positive electrode current collector through the positive temperature coefficient material layer, an internal short circuit will occur due to the small resistance of the positive temperature coefficient material, generating a large amount of Joule heat, causing the internal temperature of the battery cell to rise. When the temperature exceeds the Curie point of the positive temperature coefficient material, the resistance of the positive temperature coefficient material increases stepwise, which will quickly reduce the internal short circuit heat generation power and reduce the risk of thermal runaway after the internal short circuit of the battery cell. Thus, the safety of the battery cell is improved. In addition, the PTC material has good compatibility with the positive electrode active material (also referred to as "positive electrode material" in this application), and can be evenly coated on the edge of the positive electrode material, and it is not easy for the positive electrode current collector to leak out due to the gap between the PTC material and the positive electrode material. At the same time, the positive temperature coefficient material is not easy to fall off from the positive electrode collector, and can block the contact between the negative electrode material and the positive electrode ear or the positive electrode collector throughout the entire life cycle.

[0043] However, if the PTC material is dispersed in the positive electrode active material layer, or the PTC material is directly coated on the current collector surface, although thermal runaway can be prevented during an internal short circuit, the PTC material also has a certain resistance, which will increase the internal resistance of the battery cell, thereby reducing the electrochemical performance of the battery, such as charge and discharge performance. According to the mechanism, the PTC material is set in the positive electrode current collector area corresponding to the overhang area where thermal runaway is most likely to occur, which can maximize the function of the PTC material in preventing internal short thermal runaway without affecting the electrochemical performance of the battery.

[0044] It can be understood that when both sides of the positive electrode current collector include positive electrode active material layers, both sides also include PTC material layers.

[0045] According to an embodiment of the present application, the positive temperature coefficient material includes an organic matrix, an inorganic filler and an adhesive filler. The organic matrix provides a skeleton structure for the PTC material so that it has a suitable shape and mechanical strength, etc. The inorganic filler is filled in the organic matrix to form a conductive channel at room temperature, so that the PTC material has conductivity. As the temperature increases, the contact between the inorganic fillers decreases, resulting in a rapid increase in resistance. The adhesive filler is used to bond the organic matrix and the inorganic filler as well as the PTC material and the positive electrode current collector, thereby improving the stability of the material during the battery charging and discharging process.

[0046] According to an embodiment of the present application, the organic matrix includes at least one of polyethylene, polyethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polyhexafluoropropylene, polyhexafluoropropylene copolymer, polyamide, polyamide copolymer, polyurethane and polyurethane copolymer. Thus, a skeleton structure of the PTC material is provided, so that the PTC material further has more suitable mechanical properties, wear resistance, corrosion resistance and electrical insulation.

[0047] According to an embodiment of the present application, the inorganic filler includes at least one of barium titanate and strontium titanate. The inorganic filler is a PTC material, which has high conductivity at room temperature and can quickly increase resistance when the temperature rises to a threshold, thereby preventing thermal runaway.

[0048] According to an embodiment of the present application, the adhesive filler includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and polyacrylate, thereby improving the stability of the PTC material.

[0049] According to an embodiment of the present application, the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.2~0.9):(0.1~0.5):(0.05~0.2), for example, it can be 0.2:0.1:0.05, 0.2:0.1:0.1, 0.2:0.1:0.15, 0.2:0.1:0.2, 0.4:0.2:0.1, 0.6:0.5:0.15, 0.9:0.3:0.08, etc.

[0050] The organic matrix, inorganic filler and adhesive filler in the PTC material meet the above ratio, which can make the PTC material maintain a low resistance at a temperature below the Curie point, thereby reducing the adverse effect on the normal operation of the battery. At the same time, the PTC material that meets the above ratio has a suitable Curie point, which can avoid the failure to increase the resistance in time when the battery is overheated due to the Curie point being too high, or the sudden increase in resistance of the battery during normal use due to the Curie point being too low, affecting the battery performance. In addition, this ratio also enhances the compatibility of the PTC material with the positive electrode material, allowing it to be evenly coated on the edge of the positive electrode collector, reducing the gap between the PTC material and the positive electrode material and the leakage of the positive electrode collector, while improving the bonding strength with the positive electrode collector, reducing the risk of material shedding, and effectively reducing the possibility of thermal runaway, thereby significantly improving the safety of the battery.

[0051] According to an embodiment of the present application, the positive electrode active material layer includes lithium iron phosphate or lithium manganese iron phosphate, and the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.35~0.5):(0.4~0.45):(0.1~0.2), for example, it can be 0.35:0.4:0.1, 0.4:0.45:0.15, 0.5:0.4:0.1, 0.45:0.45:0.2, etc.

[0052] Based on the characteristics of lithium iron phosphate positive electrode active materials, the PTC material with the above-mentioned ratio of organic matrix, inorganic filler and adhesive filler has a suitable Curie point. The PTC material maintains a low resistance at a temperature below the Curie point, thereby reducing the adverse effect on the normal operation of the battery. The resistance of the PTC material will increase rapidly at a temperature above the Curie point, thereby reducing the possibility of thermal runaway. In addition, this ratio also enhances the compatibility of the PTC material with lithium iron phosphate, and can be evenly coated on the edge of the positive current collector, reducing the gap between the PTC material and lithium iron phosphate and the leakage of the positive current collector, while improving the bonding strength with the positive current collector, reducing the risk of material shedding, and effectively reducing the possibility of thermal runaway, thereby significantly improving the safety of the battery.

[0053] According to an embodiment of the present application, the positive electrode active material layer includes lithium iron phosphate, and the Curie point of the positive temperature coefficient material is 120°C to 145°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C;

[0054] Alternatively, the positive electrode active material layer includes lithium manganese iron phosphate, and the Curie point of the positive temperature coefficient material is 115°C to 136°C, for example, 115°C, 120°C, 125°C, 130°C, 135°C, or 136°C.

[0055] The Curie point of the PTC material meets the above conditions, which can make the PTC material have a low resistance when the battery is in normal use, and the resistance increases rapidly when the temperature rises abnormally, thereby effectively reducing the possibility of thermal runaway and significantly improving the safety of the battery.

[0056] Exemplarily, the Curie point of a positive temperature coefficient material can be determined by:

[0057] The positive electrode collector area with the PTC material layer cut out on the positive electrode sheet was taken, and the resistivity was detected at 20°C, 60°C, 100°C, 120°C, and 140°C using a temperature-controllable 16-probe resistance meter. The resistivity at different temperatures was plotted, and the inflection point of the curve was recorded as the Curie point.

[0058] According to an embodiment of the present application, the positive electrode active material layer includes a ternary positive electrode material, and the mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.7~0.85):(0.1~0.2):(0.05~0.1), for example, it can be 0.7:0.1:0.05, 0.7:0.2:0.05, 0.75:0.1:0.08, 0.8:0.15:0.08, 0.85:0.2:0.1, etc.

[0059] Based on the characteristics of the ternary positive electrode active material, the PTC material with the above-mentioned ratio of organic matrix, inorganic filler and adhesive filler has a suitable Curie point. The PTC material maintains a low resistance at a temperature below the Curie point, thereby reducing the adverse effect on the normal operation of the battery. The PTC material will experience a rapid increase in resistance at a temperature above the Curie point, thereby reducing the possibility of thermal runaway. In addition, this ratio also enhances the compatibility of the PTC material with the ternary positive electrode active material, and can be evenly coated on the edge of the positive electrode collector, reducing the gap between the PTC material and the ternary positive electrode active material and the leakage of the positive electrode collector, while improving the bonding strength with the positive electrode collector, reducing the risk of material shedding, and effectively reducing the possibility of thermal runaway, thereby significantly improving the safety of the battery.

[0060] According to an embodiment of the present application, the ternary positive electrode material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese aluminum oxide.

[0061] According to an embodiment of the present application, a positive electrode active material layer 240 is further provided on the surface of the positive electrode current collector 210 facing the negative electrode plate 100, and the positive electrode active material layer 240 is connected to the side of the positive temperature coefficient material layer 230 away from the positive electrode tab 220, and the projection of the positive electrode active material layer 240 toward the negative electrode active material layer 110 overlaps with the area of ​​the negative electrode active material layer 110 except for the excess area 120.

[0062] According to an embodiment of the present application, the thickness of the positive temperature coefficient material layer 230 is 20 μm to 60 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm. Thus, it is easy to form a film layer with uniform thickness, the inside of the film layer is evenly heated, and the response speed to temperature changes is fast.

[0063] According to an embodiment of the present application, along the direction from the positive electrode current collector 210 to the positive electrode tab 220, the width of the positive temperature coefficient material layer 230 is 1 mm to 5 mm, for example, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm. Thus, the positive projection of the PTC material layer toward the negative electrode sheet is located in the overhang area or exceeds the overhang area.

[0064] According to an embodiment of the present application, the method for preparing the positive temperature coefficient material includes:

[0065] The organic matrix, the inorganic filler and the adhesive filler are subjected to a first pulverization process to obtain a first pulverized product;

[0066] performing a first drying process on the first pulverized product to obtain a first dried product;

[0067] The first dried product is fired to obtain a fired product;

[0068] The fired product is subjected to a second pulverization treatment to obtain a second pulverized product;

[0069] The second pulverized product is subjected to a second drying process to obtain the positive temperature coefficient material.

[0070] According to an embodiment of the present application, the first pulverization process includes: mixing the organic matrix, the inorganic filler, the adhesive filler and the first solvent by ball milling at a rotation speed of 20 Hz to 40 Hz for 1 h to 3 h, wherein the solvent includes anhydrous ethanol and isopropanol, so as to make the materials more refined and evenly dispersed.

[0071] According to an embodiment of the present application, the temperature of the first drying treatment is 80° C. to 100° C. and the time is 4 h to 8 h, so as to remove the solvent and moisture and avoid interference with subsequent firing.

[0072] According to an embodiment of the present application, the firing process satisfies at least one of the following conditions:

[0073] The temperature was raised from 20°C~25°C to 800°C~1100°C at a heating rate of 5°C / min~10°C / min;

[0074] The firing time is 2 h to 3 h.

[0075] Therefore, firing according to the above conditions can make the material fully formed without denaturation.

[0076] According to an embodiment of the present application, before the calcination process, the first dried material is passed through a 80-100 mesh sieve, so as to screen out materials that meet the particle size requirements.

[0077] According to an embodiment of the present application, the second pulverization treatment condition includes: mixing the fired product with the first solvent by ball milling at a rotation speed of 20 Hz to 40 Hz for 1 h to 3 h, wherein the solvent includes anhydrous ethanol and isopropanol, so as to make the material more refined and evenly dispersed.

[0078] According to an embodiment of the present application, the temperature of the second drying treatment is 80° C. to 100° C. and the time is 4 h to 8 h, so as to remove the solvent and moisture and avoid interference with subsequent firing.

[0079] According to an embodiment of the present application, the method further comprises: sieving the positive temperature coefficient material and mixing it with a second solvent to obtain a solution containing the positive temperature coefficient material;

[0080] The screening includes passing through a 80-mesh to 100-mesh sieve, thereby screening out materials that meet the particle size requirements;

[0081] The second solvent includes N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF).

[0082] According to an embodiment of the present application, the positive electrode current collector 210 may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0083] According to an embodiment of the present application, the positive active material layer 240 may further include a conductive agent, for example, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0084] According to an embodiment of the present application, the positive electrode active material layer 240 may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0085] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0086] According to an embodiment of the present application, the negative electrode plate 100 further includes: a negative electrode current collector 130 and a negative electrode tab 140 . The negative electrode current collector 130 is arranged on a side of the negative electrode active material layer 110 away from the positive electrode plate 200 , and the negative electrode tab 140 is connected to the negative electrode current collector 130 .

[0087] According to an embodiment of the present application, the negative electrode current collector 130 may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0088] According to an embodiment of the present application, the negative electrode active material may adopt a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0089] According to an embodiment of the present application, the negative electrode active material layer 110 may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0090] According to an embodiment of the present application, the negative electrode active material layer 110 may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0091] According to an embodiment of the present application, the negative electrode active material layer 110 may further optionally include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0092] According to an embodiment of the present application, a negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet (such as negative electrode active material, conductive agent, binder and any other components) are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing and other processes, a negative electrode sheet can be obtained.

[0093] The present invention has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0094] The second aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes the battery cell described in the first aspect. The features and advantages described above for the battery cell described in the first aspect are also applicable to the battery and will not be repeated here.

[0095] According to an embodiment of the present application, the battery may include an outer package for packaging the positive electrode sheet, the negative electrode sheet and the electrolyte.

[0096] According to an embodiment of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0097] According to an embodiment of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0098] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0099] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0100] The third aspect of the present invention provides an electric device. According to an embodiment of the present application, the electric device includes the battery of the second aspect. Therefore, the electric device of the present application has high-efficiency energy output and excellent service life and safety performance.

[0101] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0102] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0103] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0104] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0105] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0106] Example 1

[0107] 1. Preparation of positive electrode sheet

[0108] (1) The positive electrode active material LiFePO4, the conductive agent carbon black, and the binder PVDF were fully mixed in a mass ratio of 95:2.5:2.5, and the solvent NMP was added. The mixture was stirred under the action of a vacuum stirrer until the slurry was uniformly mixed to obtain a positive electrode slurry.

[0109] (2) Put polyethylene, barium titanate and polyvinylidene fluoride into a planetary ball mill in a ratio of 0.7:0.2:0.1, use anhydrous ethanol as the grinding medium, and ball mill at a speed of 40 Hz for 2 hours. After ball milling, the slurry is dried at 100°C for 6 hours to remove the anhydrous ethanol in the slurry. The dried powder is passed through a 100-mesh sieve and placed in a muffle furnace. The temperature is raised from room temperature to 1100°C at a rate of 5-10°C / min for 2 hours. The powder obtained after firing is put into a planetary ball mill for secondary grinding, still using anhydrous ethanol as the grinding medium. The relevant process parameters are the same as the first ball milling process. The ball-milled slurry is placed in an oven at 80-100°C for drying, and the granulated powder is passed through an 80-mesh sieve. The powder is mixed with NMP at a solid content ratio of 55%-70%, and fully mixed in an ultrasonic oscillator with a power of 1000 W for 8 hours to obtain a mixed solution of PTC material.

[0110] (3) The positive electrode slurry is evenly coated on both surfaces of the current collector aluminum foil with a coating thickness of 75 μm, and a 3 mm wide area is reserved at the edge of one end of the current collector to be connected to the positive electrode tab without coating the positive electrode slurry. PTC material is coated on the reserved area to form a PTC material layer with a thickness of 40 μm. After the electrode sheet is completely dried, it is rolled and die-cut to obtain the positive electrode sheet.

[0111] Preparation of negative electrode sheets: Mix negative electrode active material graphite, conductive agent carbon black, binder SBR, and thickener CMC in a mass ratio of 93:1:4:2, add solvent deionized water, and stir under the action of a vacuum mixer until the slurry is uniformly mixed to obtain negative electrode slurry; evenly coat the negative electrode slurry on both surfaces of the collector copper foil, and after the electrode sheet is completely dried, roll and die-cut to obtain the positive electrode sheet.

[0112] 3. Preparation of electrolyte

[0113] In an argon glove box, ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain a mixed solvent. Lithium hexafluorophosphate (LiPF6), vinylene carbonate (VC), methylene disulfonate (MMDS), and 2,6-di-tert-butyl-4-methylphenol (BHT) were added to the mixed solvent to obtain an electrolyte. Based on the total mass of the electrolyte, the mass proportion of lithium hexafluorophosphate was 12%, the mass proportion of vinylene carbonate was 5%, the mass proportion of methylene disulfonate was 1%, and the mass proportion of 2,6-di-tert-butyl-4-methylphenol was 0.5%.

[0114] 4. Isolation film

[0115] The diaphragm is a PE-coated ceramic diaphragm with a thickness of 12µm.

[0116] 5. Lithium-ion battery preparation

[0117] Stack the negative electrode sheet, separator, positive electrode sheet, and separator in order, repeat the above order and fix them with high temperature resistant tape, then weld the positive and negative electrode tabs, where the positive electrode tab is welded to the PTC material layer side of the positive current collector, and encapsulate with aluminum plastic film to obtain the battery cell. The width of the PTC material layer is 1.5mm (such as Figure 3 After the battery cell is vacuum dried at 80°C for 72 hours (along the positive electrode active material layer toward the positive electrode ear), the corresponding prepared electrolyte is injected and packaged, and then a lithium-ion battery is obtained through the steps of standing, pressurized formation, aging, exhausting, and capacity division.

[0118] The differences between Examples 2 to 14 and Example 1 are shown in Table 1.

[0119] Comparative Example 1

[0120] The difference from Example 1 is that step (2) is not included;

[0121] Step (3) is as follows:

[0122] The positive electrode slurry was evenly coated on both surfaces of the current collector aluminum foil with a coating thickness of 75 μm. After the electrode sheet was completely dried, it was rolled and die-cut to obtain the positive electrode sheet.

[0123] Comparative Example 2

[0124] The difference from Example 1 is that step (2) is as follows: boehmite, polyvinylidene fluoride and NMP are fully stirred and mixed in a ratio of 0.5:0.1:0.4 to obtain a ceramic slurry.

[0125] In step (3), a ceramic material is coated on the reserved area to form a ceramic layer.

[0126] Comparative Example 3

[0127] The difference from Example 1 is that step (3) is as follows:

[0128] The mixed solution of positive electrode slurry and PTC material is evenly coated on both surfaces of the current collector aluminum foil with a coating thickness of 75 μm. After the electrode sheet is completely dried, it is rolled and die-cut to obtain the positive electrode sheet.

[0129] Performance Testing

[0130] 1. The batteries prepared in Examples 1 to 14 and Comparative Example 2 were subjected to performance tests respectively. The specific test methods are as follows:

[0131] Average value of the gap between the PTC material layer and the positive electrode active material layer: collected online during the coating process using a high-resolution CCD camera.

[0132] PTC material layer peeling force value: measured offline by a tensile testing machine.

[0133] PTC material layer shedding: After the lithium-ion battery is cycled a certain number of times in accordance with GB / T31484-2015 "Cycle life requirements and test methods for power batteries for electric vehicles", the battery cell is disassembled and the coating layer is observed to see if it has shedding.

[0134] Volume resistivity: Cut out the positive electrode current collector area with the PTC material layer on the positive electrode sheet, use a temperature-controllable 16-probe resistance meter to detect the resistivity at 20℃, 60℃, 100℃, 120℃, and 140℃, respectively, plot the resistivity at different temperatures, and record the inflection point of the curve as the Curie point.

[0135] The results are shown in Table 1. The battery performance of Examples 1 to 14 is better than that of Comparative Example 2. In Comparative Example 2, ceramic materials are used to replace PTC materials. Due to the poor compatibility of ceramic materials with positive electrode active materials, the gap between the coating area and the positive electrode active material layer is large, and the coating area has uneven thickness. In addition, the peeling force between the ceramic material and the current collector is low, and the ceramic layer is prone to fall off.

[0136] In the LiFePO4 system of Example 1 and Example 2, the Curie point meets the optimal condition of 120°C to 145°C, and in the nickel cobalt manganese oxide system of Example 10, the Curie point meets the optimal condition of 90°C to 110°C. Thus, the PTC material can have a low resistance when the battery is in normal use, and the resistance increases rapidly when the temperature rises abnormally, thereby effectively reducing the possibility of thermal runaway and significantly improving the safety of the battery.

[0137] It can be seen from Examples 1, 4, 9 and 10 that a high proportion of the organic matrix will result in a low Curie point, causing a sudden increase in resistance of the battery during normal use, thus affecting battery performance.

[0138] It can be seen from Examples 1 and 5, and Examples 9 and 11 that a low proportion of the organic matrix will result in a low Curie point, which will cause a sudden increase in resistance of the battery during normal use, affecting battery performance.

[0139] It can be seen from Examples 1 and 6, and Examples 9 and 12 that a high proportion of inorganic fillers will result in a high Curie point, which will cause the PTC material to fail to increase resistance in time when the battery is overheated, reduce heat generation power, and fail to perform its due function.

[0140] It can be seen from Examples 1 and 7, and Examples 9 and 13 that a low proportion of inorganic filler will result in a low Curie point, which will cause a sudden increase in resistance of the battery during normal use, affecting battery performance.

[0141] It can be seen from Examples 1 and 8, and Examples 9 and 14 that if the ratio of adhesive filler is too low, the coating layer may easily fall off in the later stage of the cycle, resulting in the aluminum foil in the overhang area being exposed, causing the consequence of an internal short circuit. If the ratio of adhesive filler is too high, the manufacturing process will be difficult.

[0142] Table 1

[0143]

[0144] 2. The batteries prepared in Example 1 and Comparative Examples 1-3 were subjected to thermal runaway tests respectively, and the specific steps are as follows:

[0145] Mark the battery, disassemble the battery in the glove box, cut and remove the diaphragm in the overhang area facing the positive projection area of ​​the diaphragm, and then re-seal the battery. Perform a cycle test in accordance with GB / T31484-2015 "Requirements and Test Methods for Cycle Life of Power Batteries for Electric Vehicles" and monitor the battery voltage and temperature. If the cell voltage drops by more than 25% of the initial value, and the temperature rise rate dT / dt at the monitoring point is ≥1℃ / s and lasts for more than 3s, it is judged as thermal runaway of the cell in accordance with GB38031.

[0146] The results are shown in Table 2. In Example 1, since a PTC material layer is provided on the positive current collector, when the diaphragm is damaged and the negative active material layer at the edge of the negative electrode plate contacts the positive electrode tab through the PTC material layer, the internal short circuit generates a large amount of Joule heat, causing the temperature of the contact point to rise. When the temperature exceeds the Curie point of the PTC material, the resistance of the positive temperature coefficient material increases, which will quickly reduce the internal short circuit heat generation power, allowing the battery's electrical energy to be slowly released, reducing the risk of thermal runaway after a short circuit occurs inside the battery cell.

[0147] In Comparative Example 1, no treatment was done on the positive electrode current collector, and internal short circuit thermal runaway occurred after a short period of cycling.

[0148] In Comparative Example 2, ceramic materials are used to replace PTC materials. After the diaphragm is damaged, the ceramic skeleton can prevent the occurrence of internal short circuits to a certain extent. However, due to the characteristics of the ceramic itself, it can only prevent the occurrence of internal short circuits for a short time. After the ceramic skeleton is broken, an internal short circuit will occur, and thermal runaway will still occur.

[0149] Comparative Example 3 disperses the PTC material in the positive electrode active material layer. Since the resistance of the PTC material increases with the increase of temperature, it can prevent thermal runaway to a certain extent during internal short circuit, which is slightly better than not mixing the PTC material (Comparative Example 1), but significantly worse than Example 1. In addition, since the PTC material has a certain resistance, it will increase the internal resistance of the battery cell, thereby reducing the electrochemical performance of the battery, such as charge and discharge performance.

[0150] Table 2

[0151]

[0152] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A battery cell, characterized in that: include: A negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer; A positive electrode sheet, the positive electrode sheet comprising a positive electrode collector and a positive electrode tab, the positive electrode collector being connected to the positive electrode tab, a positive temperature coefficient material layer being provided on a surface of one side of the positive electrode collector facing the negative electrode sheet near an edge of one end of the positive electrode tab, the positive temperature coefficient material layer comprising a positive temperature coefficient material; A diaphragm, the diaphragm being located between the positive electrode sheet and the negative electrode sheet; At least a portion of the positive temperature coefficient material layer's orthographic projection toward the negative electrode sheet is located in a region where the negative electrode sheet exceeds the positive electrode sheet; the positive electrode tab's orthographic projection toward the negative electrode sheet is located outside the negative electrode sheet; The positive electrode current collector further comprises a positive electrode active material layer on one side of the surface facing the negative electrode plate, and the positive electrode active material layer is connected to a side of the positive temperature coefficient material layer away from the positive electrode tab; The positive temperature coefficient material comprises an organic matrix, an inorganic filler and an adhesive filler; The mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.2-0.9): (0.1-0.5): (0.05-0.2).

2. The battery cell according to claim 1, characterized in that: The organic matrix includes at least one of polyethylene, polyethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polyhexafluoropropylene, polyhexafluoropropylene copolymer, polyamide, polyamide copolymer, polyurethane and polyurethane copolymer.

3. The battery cell according to claim 1, characterized in that: The inorganic filler includes at least one of barium titanate and strontium titanate.

4. The battery cell according to claim 1, characterized in that: The adhesive filler includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and polyacrylate.

5. The battery cell according to claim 1, characterized in that: The positive electrode active material layer includes lithium iron phosphate or lithium manganese iron phosphate.

6. The battery cell according to claim 5, characterized in that: The mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.35-0.5): (0.4-0.45): (0.1-0.2).

7. The battery cell according to claim 5, characterized in that: The positive electrode active material layer includes lithium iron phosphate, and the Curie point of the positive temperature coefficient material is 120° C. to 145° C.; Alternatively, the positive electrode active material layer includes lithium manganese iron phosphate, and the Curie point of the positive temperature coefficient material is 115° C. to 136° C.

8. The battery cell according to claim 1, characterized in that: The positive electrode active material layer includes a ternary positive electrode material.

9. The battery cell according to claim 8, characterized in that: The mass ratio of the organic matrix, the inorganic filler and the adhesive filler is (0.7-0.85): (0.1-0.2): (0.05-0.1); And / or, the Curie point of the positive temperature coefficient material is 90°C to 110°C.

10. The battery cell according to claim 8, characterized in that: The ternary positive electrode material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese aluminum oxide.

11. The battery cell according to claim 1, characterized in that The thickness of the positive temperature coefficient material layer is 20 μm to 60 μm.

12. The battery cell according to claim 1, characterized in that: Along the direction from the positive electrode current collector to the positive electrode tab, the width of the positive temperature coefficient material layer is 1 mm to 5 mm.

13. A battery, characterized in that: A battery cell comprising any one of claims 1 to 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.

Citation Information

Patent Citations

  • Battery monomer, battery and electric device

    CN117878384A

  • Secondary Battery with Improved Safety and CompactStructure

    KR1020080015165A